2010 35th IEEE Photovoltaic Specialists Conference 2010
DOI: 10.1109/pvsc.2010.5616896
|View full text |Cite
|
Sign up to set email alerts
|

Industrial LCP selective emitter solar cells with plated contacts

Abstract: The investigation of different selective emitter (SE) approaches [1-3] is a current trend in solar cell manufacturing. The incorporation of a local high phosphorous doping underneath the front contact grid allows for the use of high-sheet resistance illuminated emitters that combine low recombination and improved blue response. Further efficiency increase compared to the standard screen-printed solar cell is achieved via plated contacts [4-5] that feature better aspect ratio and optical properties [6], higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 1 publication
0
14
0
1
Order By: Relevance
“…For dry laser‐doping, the concentration of the phosphorus dopant source and spin‐coating conditions as well as the laser parameters can affect the properties of the laser‐doped regions and consequently also the subsequent LIP . Recent reports have demonstrated that both dry and wet approaches can result in heavily‐doped grooves, which can be metallised using LIP nickel/copper/silver or LIP nickel/silver . Because the patterning process also forms the selective‐emitter, metallisation of laser‐doped front surface grids is a self‐aligning process, thus making the technology attractive for manufacturing.…”
Section: Front‐grid Metallisationmentioning
confidence: 99%
See 1 more Smart Citation
“…For dry laser‐doping, the concentration of the phosphorus dopant source and spin‐coating conditions as well as the laser parameters can affect the properties of the laser‐doped regions and consequently also the subsequent LIP . Recent reports have demonstrated that both dry and wet approaches can result in heavily‐doped grooves, which can be metallised using LIP nickel/copper/silver or LIP nickel/silver . Because the patterning process also forms the selective‐emitter, metallisation of laser‐doped front surface grids is a self‐aligning process, thus making the technology attractive for manufacturing.…”
Section: Front‐grid Metallisationmentioning
confidence: 99%
“…For dry laser-doping, the concentration of the phosphorus dopant source and spin-coating Silicon solar cell metallisation A. Lennon, Y. Yao and S. Wenham conditions as well as the laser parameters can affect the properties of the laser-doped regions and consequently also the subsequent LIP [64]. Recent reports have demonstrated that both dry and wet approaches can result in heavilydoped grooves, which can be metallised using LIP nickel/ copper/silver or LIP nickel/silver [27,56,57,59,61,62,65].…”
Section: Laser Dopingmentioning
confidence: 99%
“…Background plating-also known as 'ghost plating' or 'parasitic plating'-is an unwated copper plating that occurs at the passivation layers. Inhomogeneities at the SiN x surface, silicon residuals and cracks are mainly responsible for background plating [99,100]. The phenomenon may affect cell performance by creating undesirable shading and can divest the solar cell aesthetically.…”
Section: Background Platingmentioning
confidence: 99%
“…Due to recrystallization velocities in the order of m/s, proper choice of processing parameters can only minimize the laser-induced crystal damage, but cannot prevent it entirely [1], [4], [5], [8], [9]. Laser processes with long pulses are also suitable for laser-induced selective doping [10]- [12]. Here, dopants from an external source diffuse rapidly within the liquid phase of the molten Si.…”
Section: Introductionmentioning
confidence: 99%